(untitled) (Romanian Studies Today, 2024)
The aim of this paper is to describe the process of evaluation which occurs in a digital environment using Exam.net, an examination platform developed by a group of Swedish teachers. The mechanism behind Exam.net was analysed during the numerous evaluation activities which took place in May and June 2020, as a part of the second semester examination at the Preparatory Year of Romanian (a full-time academic programme organised by the University of Bucharest). Based on the cloud-computing system, Exam.net is an easy-to-use and secure evaluation tool, with several technical and didactic advantages, which are explained in the present paper. The platform was created in accordance with the requirements set out by the National Agency for Education in Sweden regarding data handling and anonymisation. Nevertheless, the main advantage of Exam.net consists in the two different levels of security: the low-security mode and the high-security mode, the latter being associated with Safe Exam Browser (SEB), a type of software which prevents unauthorized resources being used during an exam. As a result, both layers of security considerably reduce the risk of examination fraud. In addition to this, Exam.net is highly reliable, given its infrastructure that automatically handles a large number of concurrent users.